The team as a secure base revisited: remote working and resilience among child and family social workers during COVID-19. Issue 4 (21st September 2020) - Cook, Laura Louise; Zschomler, Danny; Biggart, Laura; Carder, Sara
Abstract : Purpose: Social work teams can provide a secure base for social workers, supporting them to manage the emotional demands of child and family social work (Biggart et al., 2017). As the COVID-19 pandemic has necessitated increased remote working, social workers have needed to maximise their use of virtual networks and navigate new ways of connecting with colleagues. This study aims to examine the extent to which social work teams can function as a secure base in the context of remote working. Design/methodology/approach: Between 19th March and 13th June, the authors undertook 31 in-depth, qualitative interviews with child and family social workers across 9 local authorities in England. this research captured social workers' perspectives on remote working and team support throughout lockdown in England. Findings: In this study, the authors report findings in three key areas: how social workers experienced the sudden shift to increased remote working; how social work teams provided a secure base for remote working; and the challenges for sustaining the team as a secure base when working remotely. Originality/value: These findings will be of interest to social workers, managers and local authorities as they adapt to the challenges of increased remote working in child and family social work.